Comprehensive Analysis of the Clinical and Biological Significances of Endoplasmic Reticulum Stress in Diffuse Gliomas - Huang, Ruoyu; Li, Guanzhang; Wang, Kuanyu; Wang, Zhiliang; Zeng, Fan; Hu, Huimin; Jiang, Tao (Frontiers in Cell and Developmental Biology, 2021)
Background: As a critical organelle for protein and lipid synthesis, the dysfunction of endoplasmic reticulum has a significant impact on multiple biological processes of cells. Thus, in this study, we constructed an ER stress-related risk signature to investigate the functional roles of ER stress in gliomas. Methods: A total of 626 samples from TCGA RNA-seq dataset (training cohort) and 310 samples from CGGA RNA-seq dataset (validation cohort) were enrolled in this study. Clinical information and genomic profiles were also obtained. The ER stress signature was developed by the LASSO regression model. The prognostic value of the risk signature was evaluated by Cox regression, Kaplan-Meier and ROC Curve analyses. Bioinformatics analysis and experiment in vitro were performed to explore the biological implication of this signature. Results: We found that the ER stress-related signature was tightly associated with major clinicopathological features and genomic alterations of gliomas. Kaplan-Meier curve and Cox regression analysis indicated that ER stress activation was an independent prognostic factor for patients with glioma. Besides, we also constructed an individualized prognosis prediction model through Nomogram and ROC Curve analysis. Bioinformatics analysis and cell biology experiments suggested that ER stress activation also promoted the malignant progression of glioma and participated in the regulation of tumor immune microenvironment, especially the infiltration of macrophages in M2 phase. Conclusion: The ER stress activation had a high prognostic value and could serve as a promising target for developing individualized treatment of glioma.